UniQ-Typer ™ Y-10 genotyping in South African populations: novel alleles, sequence variation and allelic ladder updates. Issue 1 (December 2019) - Kasu, Mohaimin; Fraser, Mischa; D'Amato, Maria Eugenia
Abstract: DNA profiling the male specific region on the Y-chromosome is fundamental to forensic practise. It is recognised as a powerful tool for sexual assault investigations for resolving the male DNA components, for familial search and as a tool to aid biogeographic inferences. In this study the novel Y-chromosome Short Tandem Repeat (Y-STR) multiplex called the UniQ-Typer ™ Y-10 was utilised for population wide genotyping in South Africa. In this study we provide a significant updated to the genotyping allelic ladder for the panel and report novel variation which gave strong signals to potentially infer biogeographic ancestry.